Implementation of Policy on Development of Forest Management Units (KPH) in West Nusa Tenggara Province - Mukarom, Madani; Suradinata, Ermaya; Mulyati, Detty; Muhi, Ali Hanafiah (International Journal of Science and Society, 2023)
Damage to forests outside Java, including West Nusa Tenggara (NTB), is largely due to the absence of forest management units (FMUs) at the site level, resulting in open access areas prone to illegal logging and deforestation. The establishment of FMUs is mandated by Law 41/1999 and Government Regulations 6/2007 and 3/2008. Since 2008, NTB has initiated FMU development through area designations and the issuance of governor regulations. By 2016, four provincial FMUs and nine district FMUs were established. However, Law 23/2014 shifted forest management authority to the provincial level. This study examines the implementation of FMU development policies in NTB, applying Van Meter and Van Horn's public policy theory, a qualitative descriptive approach, and ASOCA strategy analysis, verified through triangulation techniques. The findings highlight several supporting factors, including forest management authority, regional leadership commitment, local regulations, and long-term planning. Conversely, challenges include reduced authority under Law 11/2020, limited budget capacity, widespread encroachment, and weak provincial-district coordination. Despite these challenges, the policy implementation in NTB is considered effective, evidenced by the establishment of 15 FMUs and one nature park, as well as the enactment of Regional Regulation 14/2019 on forest management. A new AN KHAN policy strategy model is proposed to accelerate FMU development in the region.